CORRELATION BETWEEN PARENTING PATTERN AND MPASI-GIVING PATTERN TO NUTRITIONAL STATUSOF INFANTS AGED 6-12 MONTHS IN MEKARGALIH VILLAGE (Proceedings of the International Conference on Public Health, 2017)
The quantity and quality of food given to the child is important to be thought of, planned, and implemented by their mother or caregiver. Parenting is always associated with the act of food-giving. The purpose of this study was to determine whether parenting pattern and the pattern of MPASI (Makanan Pendamping Asi/Weaning Food)-giving are related to the nutritional status of infants aged 6-12 months in Mekargalih Village. The method used in this study was the analytical method, with cross sectional approach. This study took samples from 64 respondents. The data collection was done with questionnaires and infants weighing.The data analysis was done by using chi-square test. The result of the research regarding mothers’ parenting pattern in the terms of attention/support and psychosocial stimulation were in the ‘good’ category for 63 respondents (98,4%). The pattern of MPASI-giving in infants aged 6-12 months, that is the MPASI-giving age that stretches for the period of 6 months, was confirmed by 45 respondents (70.3%) and the type of MPASI given is the combination of weaning food and breast milk for 43 respondents (67,2%) with the frequency of 3-4 times a day for 50 respondents (78,1%). Most infants, or 49 babies (76,6%), had good nutritional status. The p> 0,05 chi-square test result showed that there was no significant correlation between parenting pattern to infants’ nutritional status at the age 6-12 month and further study also showed no significant correlation between MPASI-giving pattern to infants’ nutritional status. This study concluded that there was no correlation between parenting pattern and MPASI-giving pattern to nutritional status, because p> 0,05.
Keywords: Parenting pattern, MPASI-giving pattern, nutritional status